2022
DOI: 10.1021/acsnanoscienceau.2c00025
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Nanoparticles of Multimetallic Phosphides via Precursor Tuning: Ternary and Quaternary M2P Phases (M = Fe, Co, Ni)

Abstract: Transition metal phosphides (TMPs) are a highly investigated class of nanomaterials due to their unique magnetic and catalytic properties. Although robust and reproducible synthetic routes to narrow polydispersity monometallic phosphide nanoparticles (M2P; M = Fe, Co, Ni) have been established, the preparation of multimetallic nanoparticle phases (M2–x M′ x P; M, M′ = Fe, Co, Ni) remains a significant challenge. Colloidal syntheses employ zero-valent metal carbonyl or multivalent acetylacetonate salt precursor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The choice of metal precursor also influences phase formation v ia different reactivities of the metal or the attached anions. The Brock group found different reactivity in Fe, Ni, and Co precursors when forming M 2 P particles (at 300 °C) . They used metal acetylacetonate salts and metal carbonyls with trioctylphosphine, oleylamine, and octadecene to explore monometallic and multimetallic transition metal phosphides.…”
Section: Phase Control Of the Metal Pnictidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of metal precursor also influences phase formation v ia different reactivities of the metal or the attached anions. The Brock group found different reactivity in Fe, Ni, and Co precursors when forming M 2 P particles (at 300 °C) . They used metal acetylacetonate salts and metal carbonyls with trioctylphosphine, oleylamine, and octadecene to explore monometallic and multimetallic transition metal phosphides.…”
Section: Phase Control Of the Metal Pnictidesmentioning
confidence: 99%
“…They also found that rate of phosphidation was much slower for Fe­(CO) 5 than for Co 2 (CO) 8 and Ni­(acac) 2 , overall showing metal precursor reactivity should be taken into account when synthesizing metal phosphides. When forming trimetallic phosphides, the order addition of the metals was key to success because of the different amorphous intermediates that formed . While the Brock group focused on reactivity of different metals, precursors of the same metal also show varying reactivity.…”
Section: Phase Control Of the Metal Pnictidesmentioning
confidence: 99%
“…Similarly, colloidal high entropy metal phosphide nanoparticles have not yet been reported, although progress has been made in targeting three-metal colloidal phosphide nanoparticles. 50 In general, high entropy chalcogenide and phosphide nanoparticles have been slower to emerge than alloy systems, despite the frequency with which single-metal chalcogenide and phosphide colloidal nanoparticles are synthesized. To make metal sulfide and phosphide nanoparticles, one must react metal salts and/or complexes with chalcogen or phosphide reagents.…”
Section: Colloidal High Entropy Chalcogenide and Phosphide Nanoparticlesmentioning
confidence: 99%
“…Solvothermal methods have been reported to produce a limited number of high entropy metal sulfide nanoparticles, but to our knowledge, high entropy metal selenide and telluride nanoparticles have not yet been reported using colloidal synthesis techniques. Similarly, colloidal high entropy metal phosphide nanoparticles have not yet been reported, although progress has been made in targeting three-metal colloidal phosphide nanoparticles . In general, high entropy chalcogenide and phosphide nanoparticles have been slower to emerge than alloy systems, despite the frequency with which single-metal chalcogenide and phosphide colloidal nanoparticles are synthesized.…”
Section: What Types Of Colloidal High Entropy Nanoparticles Have Been...mentioning
confidence: 99%
“…Traditional synthesis methods for TMPs via impregnation of metal and phosphorus salts on high surface area metal-oxide supports followed by high temperature reduction can lead to broad particle size distributions, overreduction of metal salts to metal NPs, non-uniform phosphorus incorporation, and excess phosphate species that do not participate in TMP formation. 24,25 Solution synthesis routes, on the other hand, can enable control over composition, particle morphology, and crystal structure, 22,[26][27][28][29][30][31][32] providing model systems to understand the role of the second metal. Our group has previously established solution synthesis approaches to obtain Ni 2 P, Rh 2 P, and a variety of alloyed Ni 2 P NPs via the thermolysis of low-valent metal triphenylphosphine complexes.…”
Section: Introductionmentioning
confidence: 99%